Calculation of a Drive with a Worm Gear Transmission (Texas Journal of Engineering and Technology, 2022)
The article discusses the conceptual requirements of the project, standardization and unification were widely used, as well as worm gears are necessary to work with small gear ratios. It is due to such a gearbox that the smooth operation of the mechanism is ensured and a low noise level is achieved